TEACHER AND STUDENT RELATIONSHIP AND TEACHING IN COURSE OF TEACHER TRAINING: A CASE STUDY IN THE FIELD OF PHYSICAL EDUCATION (Fiep Bulletin - online, 2013)
Analyzes the discussions about issues that surround higher education. Focuses specifically in the teacher and student relationship and its importance in the teaching-learning process. Highlights the following issues: requirements and challenges of teaching in higher education and the teacher-student relationship in the process of teaching-learning in higher education. This is a field study that outlines dialogue mainly with the production in the area of Education linked to Teaching in Higher Education and it presents as the main findings and conclusions the need to think about teaching in higher education referred to the analysis of teacher training, resulting in challenges and demands in the training of teachers. It appears that the identity of a university professor needs to be formed in mediation reflexive, that is, in research work with knowledge.